Hubungan Usia, Pekerjaan dan Pendidikan Pasien Terhadap Tingkat Pengetahuan DAGUSIBU di Puskesmas Wilayah Lampung Tengah - Sitepu, Debora Egyita; Primadiamanti, Annisa; Safitri, Erika Indah (Jurnal Ilmiah Wahana Pendidikan, 2024)
The DAGUSIBU movement aims to realize the rational use of medicine, people must know how to obtain, use, store and dispose of drugs properly. The purpose of this study is to determine the relationship between age, education and work of patients on DAGUSIBU knowledge at the Central Lampung Regional Health Center. This study used observational analytical methods with a cross-sectional approach. The sampling technique was carried out using the quota sampling method so that samples were obtained by all patients at the Seputih Besar Health Center, Suko Binangun Health Center, Seputih Mataram Health Center, Jati Datar Health Center and Rama Indra Health Center which met the inclusion criteria and exclusion criteria as many as 220 respondents with 44 respondents per puskesmas. The results of this study obtained age characteristics, namely early adulthood (26-35 years) as many as 62 respondents (28.18%), job characteristics, namely housewives as many as 69 respondents (31.36%), educational characteristics, namely secondary education as many as 191 respondents (86.82%). The result of p value.